Women, rape and justice: unravelling the rape conundrum - Jordan, Jan (Victims, culture and society, 2022)
The rape conundrum -- Rape laws; rape lore -- Seeking rape justice -- Riding the review-go-roung -- Men, masculinity and rape -- Prevening rape; challenging patriarchy -- The end is the beginning.